The Barley Uniculme4 Gene Encodes a BLADE-ON-PETIOLE-Like Protein That Controls Tillering and Leaf Patterning . Issue 1 (27th March 2015) - Tavakol, Elahe; Okagaki, Ron; Verderio, Gabriele; Shariati J., Vahid; Hussien, Ahmed; Bilgic, Hatice; Scanlon, Mike J.; Todt, Natalie R.; Close, Timothy J.; Druka, Arnis; Waugh, Robbie; Steuernagel, Burkhard; et al.
Abstract : A transcriptional coactivator acts at developmental boundaries to control vegetative branching and leaf patterning. Abstract: Tillers are vegetative branches that develop from axillary buds located in the leaf axils at the base of many grasses. Genetic manipulation of tillering is a major objective in breeding for improved cereal yields and competition with weeds. Despite this, very little is known about the molecular genetic bases of tiller development in important Triticeae crops such as barley ( Hordeum vulgare ) and wheat ( Triticum aestivum ). Recessive mutations at the barley Uniculme4 ( Cul4 ) locus cause reduced tillering, deregulation of the number of axillary buds in an axil, and alterations in leaf proximal-distal patterning. We isolated the Cul4 gene by positional cloning and showed that it encodes a BROAD-COMPLEX, TRAMTRACK, BRIC-À-BRAC-ankyrin protein closely related to Arabidopsis ( Arabidopsis thaliana ) BLADE-ON-PETIOLE1 (BOP1) and BOP2. Morphological, histological, and in situ RNA expression analyses indicate that Cul4 acts at axil and leaf boundary regions to control axillary bud differentiation as well as the development of the ligule, which separates the distal blade and proximal sheath of the leaf. As, to our knowledge, the first functionally characterized BOP gene in monocots, Cul4 suggests the partial conservation of BOP gene function between dicots and monocots, while phylogenetic analyses highlight distinct evolutionary patterns in the two lineages.